Manifestaciones religiosas de nuestra Comunidad - Olivares Coronado, Johana (2019)
The work of professional sufficiency, which I present, has as its theme of support "The religious manifestations of our community", this research has been carried out for students of the 3rd grade of secondary level of Regular Basic Education in the area of Person, Family and Human Relations. Two chapters have been elaborated, the first being the theoretical support addressing the knowledge of Cultural Identity, values and culture, religious manifestations of peoples, among other knowledge, in the second chapter the pedagogical support where the learning session is determined, its moments, the materials and resources used. Finally, it is concluded that religious manifestations are a characteristic of each culture allowing unity between communities and maintaining their spirituality and historical legacy.